Anti‐epidermal or anti‐vascular endothelial growth factor as first‐line metastatic colorectal cancer in modified Glasgow prognostic score 2' patients. Issue 3 (5th May 2015) - Dréanic, Johann; Dhooge, Marion; Barret, Maximilien; Brezault, Catherine; Mir, Olivier; Chaussade, Stanislas; Coriat, Romain
Abstract: Background: In metastatic colorectal cancer, the modified Glasgow prognostic score (mGPS) has been approved as an independent prognostic indicator of survival. No data existed on poor prognosis patients treated with molecular‐targeted agents. Methods: From January 2007 to February 2012, patients with metastatic colorectal cancer and poor predictive survival score (mGPS = 2), treated with 5‐fluorouracil‐based chemotherapy in addition to an anti‐epidermal growth factor receptor (EGFR) or anti‐vascular epidermal growth factor (VEGF) therapy, were included to assess the interest of targeted therapy within mGPS = 2' patients. Results: A total of 27 mGPS = 2' patients were included and received a 5‐fluorouracil‐based systemic chemotherapy in addition to an anti‐EGFR treatment (cetuximab; n  = 18) or an anti‐VEGF treatment (bevacizumab; n  = 9). Median follow‐up was 12.1 months (interquartile range 4.9–22). Patients were Eastern Cooperative Oncology Group (ECOG) Performance Status 1, 2, and 3 in 66% ( n  = 18), 26% ( n  = 7), and 8% ( n  = 2), respectively. Comparing anti‐EGFR and anti‐VEGF groups, median progression‐free survival was 3.9 and 15.4 months, respectively, and was significantly different ( P  = 0.046). Conversely, the median overall survival was not significantly different between the two groups ( P  = 0.15). Conclusion: Our study confirmed the poor survival of patients with mGPS = 2 despite the use of targeted therapy and identified the superiority of an anti‐VEGF treatment in progression‐free survival, without a significant benefit in the overall survival compared with the anti‐EGFR therapy. Our results deserved confirmation by a prospective clinical trial.